The Future of Healthcare: Evaluating the Impact of Emerging Technologies on Medical Care - Donoso Noroña, Riber Fabián; Gómez Martínez, Nairovys; Rodríguez Plascencia, Adisnay (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Telemedicine has proven particularly valuable in improving access to care for patients in remote areas by enabling medical consultations without the need for travel. However, the adoption of these technologies faces significant challenges, especially in terms of ethics and privacy, which requires the development of robust policies to protect patient data and ensure equitable access. Therefore, this study aims to investigate and analyze emerging technologies such as telemedicine, artificial intelligence (AI), and robotics in the transformation of healthcare. To this end, the impact on efficiency, accessibility, and the quality of care, as well as future implications in remote medicine, has been analyzed. Through the analysis of research materials and methods, the acceptance of these technologies by patients and health professionals was evaluated, where improvements in diagnostics and the optimization of surgical procedures with greater precision and less invasiveness have been valued. Furthermore, the results suggest that although telemedicine, AI, and robotics offer substantial benefits, successful implementation requires considering the needs and concerns of all users. In conclusion, it is crucial to continue the development of policies and technological innovation to maximize the benefits and ensure the safe and effective implementation of these technologies in healthcare.